Enlargement of Pearl Gourami (Trichogaster leeri Blkr) With Addition of Thyroxine Hormone (T4) In Different Fish Meal - Suparman, Agus; ', Mulyadi; ', Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted from August until October 2013 in Reservoir located in the Faculty of Fisheries and Marine Sciences University of Riau. The purpose of this study was to determine the pearl gourami with increasing doses of Thyroxine hormones (T4) in different fish meal. The method used is an experimental method and CRD with four treatments and three replications. The treatment in this study is P0 (control), P1 (2 mg Thyroxine hormone / kg of fish meal), P2 (4 mg Thyroxine hormone/kg of fish meal), and P3 (6 mg Thyroxine hormone/kg of fish meal).The best treatment in this study was obtained on addition of thyroxine hormone of 6 mg / kg of feed resulted in the growth of the absolute weight of 6.12 g, the absolute growth of 4.11 cm in length, daily growth rate of 0.086 g / day, and the fish production of 0,475 kg.Key word : hormone thyroxine, Pearl Gourami (Trichogaster leeri)